Transportation Demand Management. Insights from the mobil.TUM 2012, International Scientific Conference on Mobility and Transport. - (:unkn) unknown (My University, 2013)
Sharp increases in mobility costs will have severe consequences on accessibility. One key aim of this thesis is to raise awareness concerning the risks involved. Therefore an innovative Scan-Explore-Prepare methodology has been developed. By this, individual strategies for households as well as measures for public bodies were formulated in respect to coping with increasing mobility costs.
Keywords: Verkehrsplanung; Verkehrsnachfrage; Stadtverkehr; Fußgängerverkehr; Radverkehr; Straßenbahn; Nachhaltige Mobilität; Verkehrsverhalten; Siedlungsstruktur; Raumplanung